HYDROELECTRIC STATIONS AND THEIR IMPORTANCE FOR THE REPUBLIC OF UZBEKISTAN - Abdurauf, Abdulaziz Uulu; Xusniddinovich, Suvonov Jaxongir; Shavkatjonovich, Ahmadjonov Sayyodbek (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the significance of hydroelectric power stations in Uzbekistan, focusing on their role within the national energy infrastructure and economy. It examines the contribution of these plants to energy security and the stability of electricity supply. Methods: The research involves an assessment of the technical characteristics of existing hydroelectric power plants, analyzing their operational parameters and their overall impact on electricity generation. Additionally, economic and environmental aspects are considered to evaluate their broader influence on regional development. Results: The findings highlight the essential role of hydroelectric power plants in Uzbekistan’s energy sector. These stations contribute significantly to electricity production, enhancing the reliability of energy supply. Furthermore, they play a crucial role in supporting regional infrastructure development while offering potential economic and environmental benefits. Novelty: This study provides a comprehensive evaluation of hydroelectric power stations in Uzbekistan by integrating technical, economic, and environmental perspectives. Unlike previous studies, it emphasizes the interconnected impact of these plants on energy security, sustainability, and regional infrastructure growth.